Self-Directed Learning Readiness in Virtual Teams - Kupa, Krisztina (Tér - Gazdaság - Ember/Journal of Region, Economy and Society, 2020)
This study presents a research design, which provides a summary on the literature of virtual teams and Self-Directed Learning (SDL) and explains data collection and analytical approach of research focusing on how Self-Directed Learning Readiness Scales (SDLRS) can be applied in virtual teams. The planned research focuses on whether the SDLRS results in virtual teams will be similar to resultsin nursing education, where these scales were mostly tested. Furthermore, it will also test the assumption that members of virtual teams will score higher than participants from previous studies. The chosen SDLRS questionnaire was developed initially in 2001 and has since been tested and verified as part of the planned research. This paper gives an overview on the space, timing and methodological specifications regarding the data collection and covers the confirmatory factor analysis and descriptive statistics that will be used to analyse the data.Keywords: learning, Self-Directed Learning, virtual teams